Syair Alif Ba Ta: The poet and his mission - Noriah Mohamad (Universiti Kebangsaan Malaysia, 2003)
Syair Alif Ba Ta comprises of 72 verses in Jawi and Romanized scripts, side by side. In this work, the unknown writer used the letter A to begin the first word in each verse. As the other writer then, he referred to himself as a poor vagabond with nothing to call his own. But, he was aware that useful knowledge should be spread. He cited praises to God and reminded the readers that God has given us a mind that should be used intelligently. With knowledge, one cannot be easily fooled. Generally the syair makes good reading and understanding